Implementation of the School Literacy Movement in Instilling Student Discipline Attitudes in the Digital Era - Risma Yolanda; Nurdiyana, Nurdiyana; Sulastri, Sulastri; Setiawati, Setiawati; Suanto, Suanto (International Journal of Education, Vocational and Social Science, 2023)
The implementation of the school literacy movement must be implemented in all schools, both private and public, which aims to increase the creativity of students through literacy discipline habits. The purpose of this study was to find out how to implement the school literacy movement in instilling student discipline in the digital era at SMP Excellent 1 Tangerang and to find out the driving and inhibiting factors for implementing school literacy movement in instilling student discipline in the digital era. This study uses a qualitative approach with descriptive analysis method of data collection techniques using interviews, observation, and documentation. Based on the results of research that has been carried out using interview techniques and documentation of school principals, class teachers, and students, it shows that the school has implemented the school literacy movement, although there are still some students who are not fully disciplined in implementing the school literacy movement, the principal and class teacher provide educational punishment for students who lack discipline in literacy and become habituation for students who have implemented the school literacy movement in a disciplined manner. The driving factor for this school literacy movement is the availability of a reading corner to make it easier for students to apply a disciplined attitude to reading. However, there are still obstacles in the implementation of the school movement in instilling a disciplined attitude of students in the digital era, namely the lack of facilities and infrastructure as well as a large number of reading sources. use textbooks.